Progress in Ultrafast Intense Laser Science Volume IV - Becker, Andreas; Li, Ruxin; Chin, See Leang (Progress in Ultrafast Intense Laser Science ;, 2009)
The PUILS series presents Progress in Ultrafast Intense Laser Science, a newly emerging interdisciplinary research field spanning atomic and molecular physics, molecular science, and optical science. PUILS has been stimulated by the recent development of ultrafast laser technologies. Each volume contains approximately 15 chapters, authored by researchers at the forefront. Each chapter opens with an overview of the topics to be discussed, so that researchers, who are not experts in the specific topics, as well as graduate students can grasp the importance and attractions of this sub-field of research, and these are followed by reports of cutting-edge discoveries. This fourth volume covers a broad range of topics from this interdisciplinary research field, focusing on strong field ionization of atoms; excitation, ionization and fragmentation of molecules; nonlinear intense optical phenomena and attosecond pulses; and laser - solid interactions and photoemission.